Design analysis configuration and capacity of off-grid with implementation of photovoltaic (PV) and battery energy storage system (BESS) as power supply for shipping activities at ports - Mutiah, Fiqi; Sudiarto, Budi (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The government of Indonesia developing mitigation for climate change and achieving decarbonization in the sea transportation sector by encouraging increased use of onshore power supply for ships when berthing at ports. Off-Grid is one of the green transition technologies that provide great benefits to ports for the mitigation of environmental. To ensure optimal system operation, determining the proper configuration and component sizes is an important decision at the design stage. One of the important activities at the port is the transportation of mining products, B3 waste, and others by using ships operated with diesel engines which are known to be expensive and not environmentally friendly. The configuration consists of a photovoltaic system and an energy storage system as well as land electricity support at the port then optimized by considering solar radiation, temperature, and data component specifications to supply power to the ship so that do not use diesel generators on board. From the calculation results it is known that when the ship is anchored it requires 3,310.34 kWh/day of electrical energy. To meet electricity needs, 3,200 units of PV modules are designed with a power output of 1,216 kW peak and a BESS capacity of 4,064 kWh.